2008
DOI: 10.1158/1535-7163.mct-07-2351
|View full text |Cite
|
Sign up to set email alerts
|

αvβ3 Integrin-dependent antiangiogenic activity of resveratrol stereoisomers

Abstract: Angiogenesis is target for antineoplastic and chemopreventive therapies. The natural phytoalexin resveratrol is found in grapes and red wine as cis and trans stereoisomers. trans-Resveratrol shows antiangiogenic activity, but its mechanism of action is not fully elucidated. Recently, trans-resveratrol has been shown to interact with the B 3 integrin subunit, raising the possibility that inhibition of endothelial A v B 3 integrin function may concur to its angiosuppressive activity. To get novel insights about … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…This effect is inhibited by t-RESV, but not by c-RESV, and similar results are observed in postcapillary venules. Although a number of in vitro studies have revealed quantitative differences in the activity of the two forms, with the cis isomer appearing to be less active than its trans isomer (34)(35)(36), to our knowledge this is the first report to show that t-RESV inhibits the leukocyte-endothelial cell interactions induced by Ang-II in vivo, whereas c-RESV does not. Based on this finding, t-RESV was used in all subsequent experiments to elucidate and characterize the cardiovascular effects of RESV.…”
Section: Discussionmentioning
confidence: 71%
“…This effect is inhibited by t-RESV, but not by c-RESV, and similar results are observed in postcapillary venules. Although a number of in vitro studies have revealed quantitative differences in the activity of the two forms, with the cis isomer appearing to be less active than its trans isomer (34)(35)(36), to our knowledge this is the first report to show that t-RESV inhibits the leukocyte-endothelial cell interactions induced by Ang-II in vivo, whereas c-RESV does not. Based on this finding, t-RESV was used in all subsequent experiments to elucidate and characterize the cardiovascular effects of RESV.…”
Section: Discussionmentioning
confidence: 71%
“…However, it should be noticed that the synthetic resveratrol derivative, 3,5,4Ј-trimethoxystilbene, has been shown to cause morphological changes and development arrest of zebrafish embryos. 21) Together, these results indicate that polyphenolic compounds have different effects on embryonic development and survival of zebrafish. Abnormal development or death of curcumin treated zebrafish embryos may result from the deregulation of the functions of multiple genes.…”
Section: Dosage-dependent Toxic Effects Of Curcumin Exposurementioning
confidence: 87%
“…One of the proposed cellular mechanisms of antiangiogenic activity of resveratrol is related to the reported binding and inhibition of integrin V 3 by resveratrol 31) , which results in the inhibition of sprouting and tube formation 32) . In the present study, we demonstrated that an additional mechanism involving the ROCK pathway can contribute to the inhibitory activity of resveratrol on endothelial cell migration.…”
Section: Discussionmentioning
confidence: 99%